Kajian Yuridis Terhadap Proses Kasasi dalam Hukum Acara Perdata di Indonesia - Atikasari, Windi; Audia Rayana, Nugrahati; Maia Riska, Nadya; Najah, Lathifatun (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
This study aims to analyze the cassation process in civil procedural law in Indonesia, which is one of the important stages in dispute resolution. The main issues discussed include the procedures, requirements, and legal implications of filing a cassation. The method used is a case study with a qualitative approach, collecting data through analysis of legal documents and related literature studies. The data obtained shows that the cassation process is often an obstacle for justice seekers due to the complexity of the procedure and the length of time it takes to complete. The conclusion of this study emphasizes the importance of reform in the cassation procedure to make it more efficient and transparent, so that it can improve access and justice for the community